Short-term outcome after percutaneous coronary intervention in patients with impaired left ventricular systolic function by conventional, tissue Doppler, and speckle-tracking echocardiographic study - Mohamed M Ahmed (Wolters Kluwer Medknow Publications, 2020)
Background Myocardial revascularization with chronic left ventricular (LV) dysfunction improved LV functional and survival. Echocardiographic (echo) remains the test for assessing cardiac function in clinical practice. Tissue Doppler imaging (TDI) and speckle-tracking echocardiography (STE) are new techniques in assessing LV functions. Aim To assess the short-term outcome of LV functions after percutaneous coronary intervention (PCI) in impaired LV systolic function using conventional, tissue Doppler, and STE. Patients and methods This study included 100 patients presented with ischemic cardiac chest pain, ejection fraction (EF) less than 55%, significant coronary occlusion (>70%) in a recent angiography, and were candidates for PCI. Echo study was done before and 3 months after PCI including conventional echo and TDI of both LV functions. Moreover, two-dimensional-STE: automated function imaging is used to reflect the systolic LV function by assessment of the LV global longitudinal strain (GLS). Results Three months after PCI, there was a significant increase in LV systolic function: EF (by M-mode and modified Simpson's methods), FS (by M-mode), and mean Sm (by TDI), GLS (by STE). Moreover, LV diastolic function significantly increased: E wave velocity and E/A ratio, with no change in A wave velocity (by PW Doppler) and E' velocity and E/E' ratio (by TDI). EF measured by both M-mode and with modified Simpson's methods was significantly correlated with average Sm (by TDI) and GLS (by STE) both before and after PCI. Moreover, Sm and GLS were positively correlated both before and after PCI. There was no statistically significant correlation between E/A ratio and average E' both before and after PCI. E/A ratio was not correlated with E/E' ratio before PCI but significantly correlated after PCI. Average E' and E/E' ratio were significantly correlated before PCI but not after PCI. Conclusion Significant improvement in the global LV systolic and diastolic functions occurs after PCI in patients with baseline impaired LV systolic function owing to coronary artery disease as assessed using conventional echo, TDI, and STE.